"Performance Evaluation of Cement Mortars Containing Marble Dust and Glass Fiber Exposed to High Temperature by Using Taguchi Method", this article has been downloaded or viewed 784 times since publication. - Keleştemur, Oğuzhan (My University, 2014)
"Performance Evaluation of Cement Mortars Containing Marble Dust and Glass Fiber Exposed to High Temperature by Using Taguchi Method", this article has been downloaded or viewed 784 times since publication.
Keywords: Fırat Üniversitesi Kütüphanesi; -